Absorption Coefficient of Glass Medium – Exposed to Sodium Light using LDR - Kannan, Y.B. (Recent Research in Science and Technology, 2011)
The absorption coefficient of glass medium (green and violet color glasses) of various thicknesses, when the medium is exposed to sodium light has been studied using LDR. The value of absorption coefficient has been found almost constant in all cases as expected.